Znaczenie bajkoterapii dla małego dziecka = The importance of fairy tale therapy for a small child - Zajdel, Krzysztof (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
This article describes the importance of fairy Tales therapy for children is backed by research. It can be observed that teachers recognize the importance of this form of therapy, but it is quite unappreciated and unknown parents. What`s more, children subjected to the modern trend of media, without parental supervision, learn other values that carries Media mush.
Keywords: dziecko przedszkolne; wspomaganie dziecka; bajkoterapia; therapy through a fairy tale; child preschool; child suport